Plant DNA Recombinases: A Long Way to Go - Chittela, Rajani Kant; Sainis, Jayashree K. (Journal of Nucleic Acids, 2010)
DNA homologous recombination is fundamental process by which two homologous DNA molecules exchange the genetic information for the generation of genetic diversity and maintain the genomic integrity. DNA recombinases, a special group of proteins bind to single stranded DNA (ssDNA) nonspecifically and search the double stranded DNA (dsDNA) molecule for a stretch of DNA that is homologous with the bound ssDNA. Recombinase A (RecA) has been well characterized at genetic, biochemical, as well as structural level from prokaryotes. Two homologues of RecA called Rad51 and Dmc1 have been detected in yeast and higher eukaryotes and are known to mediate the homologous recombination in eukaryotes. The biochemistry and mechanism of action of recombinase is important in understanding the process of homologous recombination. Even though considerable progress has been made in yeast and human recombinases, understanding of the plant recombination and recombinases is at nascent stage. Since crop plants are subjected to different breeding techniques, it is important to know the homologous recombination process. This paper focuses on the properties of eukaryotes recombinases and recent developments in the field of plant recombinases Dmc1 and Rad51.